Estimation of recreation benefit for multipurpose reservoirs in Thailand - Khair, Abul; Arbhabhirama Anat; Prathet Sut abutr; I, Fude; The Canadian Government (Bangkok : Asian Institute of Technology, 1976)
Recreation visitation to two reservoirs, Bhumipol and Ubolratana in Thailand has been studied to develop mathematical expressions for the estimation of number visitors and recreation benefits. First, an existing mathematical expression, used in U.S.A. for predicting visitation, is applied in case of both the reservoirs and has been found satisfactory with a little change in the form of the expression. It is also observed that, visitation rate decreases with the increase of cost per mile. The regression analysis of collected visitation data produces equations, showing a relationship between recreation visitation and cost. Recreation benefits for both the reservoirs are estimated from a demand curve, where cost of travel distance is used in estimating price and regression equations are used for the estimation of visitation. Both kind of equations are used for this purpose. Good results are obtained when benefits are estimated on shared-cost figure basis, and when other competitive recreation sources are considered. The proposed methods may be applied in the analysis of recreation benefits for other multipurpose reservoirs of Thailand. The equations may serve in predicting visitation for other multipurpose reservoirs of similar climate, shape and facilities in Thailand.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Reservoirs -- Recreational use